Co-designing interventions to improve emergency department discharge communication with youths, parents and healthcare providers: a process evaluation - Allyson J Gallant; Janet A Curran; Mari Somerville; Lori Wozney; Christine Cassidy; Alannah Delahunty-Pike; Rebecca Mackay; Shannon MacPhee; Emma Burns; Helen Wong; Melanie Doyle; Amy Plint; et al. (International Journal of Nursing Studies Advances)
Background: Emergency departments (ED) are imperfect environments for information exchange. Communication interventions at discharge can lower readmission rates and improve adherence to follow-up. However, these interventions are rarely designed in partnership with ED clinicians, youth and their parents. Objective: To describe a theory-based co-design methodology and corresponding process evaluation to improve discharge communication for two common ED presentations: asthma and minor head injury. Methods: Eligible participants were clinicians who worked in a pediatric ED and parents and youth (aged 12–17) with recent ED experience for either presentation. Co-design teams followed a structured meeting process guided by the Behaviour Change Wheel to facilitate priority setting and intervention design. Process data was captured through meeting recordings, surveys and exit interviews. Quantitative data was analyzed using descriptive statistics and qualitative data through thematic analysis. Results: Each co-design team included eight members (n = 16) participating across eight co-design meetings (mean length: 82 min). The asthma team developed a symptom screening checklist, while the head injury team designed a concussion symptom management tool. Participants reported feeling confident in the co-design process, which increased with active engagement and seeing their decisions incorporated into intervention prototypes. Lengthy meetings and overall time commitment were issues identified by some participants across surveys and interviews. Conclusions: A theory-based co-design approach provided a useful structure to partner with youth, parents and ED clinicians to develop discharge communication tools. Consideration is needed when scheduling the timing and length of the co-design meetings to account for the schedules of both service providers and users.